Sistem Pemerintahan Desa di Desa Purba Sinomba - HUSNUL ISA HARAHAP (Politeia: Jurnal Ilmu Politik, 2011)
Purba Sinomba vilage is home to some batak people in Kecamatan Padang Bolak Kabupaten Padang Lawas Utara Sumatera Utara Province. In the past, this village has its own system of government. After a long period, the government system of the Purba Sinomba Village now fol-low the government regulation No 72/2005. This study discusses the government system of Pur-ba Sinomba village. This study aimed to clarify whether the government system of Purba Si-nomba village today, still nuanced government system that has been used previously within this area both in structure and practice. The study found that in the current system the old character has been replaced. First, the term king replaced the head of the village (kepala desa). Second, there is an election to choose a leader. Third, land is owned by residents. This phenomenon in-dicates that there is a gap between the cultural values of past and present. Its also can be inter-preted that customs and politics are two things that separated.Keywords: Village autonomy, village government, cultural values.